Psychometric properties of the Belgian coach version of the coach-athlete relationship questionnaire (CART-Q) - Balduck, A.-L.; Jowett, S. (Scandinavian Journal of Medicine & Science in Sports, 2010)
The study examined the psychometric properties of the Belgian coach version of the Coach-Athlete Relationship Questionnaire (CART-Q). The questionnaire includes three dimensions (Closeness, Commitment, and Complementarity) in a model that intends to measure the quality of the coach-athlete relationship. Belgian coaches (n=144) of athletes who performed at various competition levels in such sports as football, basketball, and volleyball responded to the CART-Q and to the Leadership Scale for Sport (LSS). A confirmatory factor analysis proved to be slightly more satisfactory for a three-order factor model, compared with a hierarchical first-order factor model. The three factors showed acceptable internal consistency scores. Moreover, functional associations between the three factors and coach leadership behaviors were found offering support to the instrument's concurrent validity. The findings support previous validation studies and verify the psychometric properties of the CART-Q applied to Belgian coaches of team sports.